Morphological Study of the Pollen Grains of Some Species belong to Genera Urtica L. and Parietaria L. (Urticaceae) in Iraq - Sultani, Aseel H. H.; Al-shemarri, KhalilI.Abass (Iraqi Journal of Science, 2022)
The paper comprise comparative palynological study of six species belong to the genera Urtica L. and Parietaria L.(P.alsinifolia Del., P.lusitanica L., P.judaicaL., U.urens L., U.dioica L., and U.pilulifera L.) of the Family Urticaceae in Iraq. All pollen grains were small size and found to be porate, Stephanoporate, Zonoporate. Characters such as shape of pollen grain, number and Dimention of pores, and Sculpturing of pollen grains were overlapped between species and of limited taxonomic value.